Composite metal catalyst, its preparation method and application in catalytic oxidation of ozone

CN122850142APending Publication Date: 2026-10-02NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610564590.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-27
Publication Date
2026-10-02

AI Technical Summary

Technical Problem

[0002]挥发性有机化合物(VOCs)作为臭氧和PM2.5的重要前体物,已成为全球大气污染治理的核心挑战之一,甲苯作为典型的芳香族VOCs,广泛来源于石油化工、涂料印刷、家具制造等行业,具有毒性强、难降解的特点,对人体健康和生态环境构成严重威胁,目前,VOCs的治理技术主要包括吸附法、焚烧法、光催化氧化法以及臭氧催化氧化法等,其中,吸附法存在吸附饱和后需频繁更换吸附剂、易产生二次污染等问题;焚烧法能耗高、运行成本大,且可能产生氮氧化物等二次污染物;光催化氧化法受限于光响应范围窄、量子效率低等瓶颈

Benefits of technology

1)本发明以可可豆荚果壳和刺苋为复合生物质,通过酸预处理协同造孔、陶瓷溶胶负压浸渍修饰孔隙结构、锰铬双金属分步负载活化等多级工艺调控,构建了兼具分级多孔结构、高机械稳定性和双金属协同催化效应的复合金属催化剂,显著提升了臭氧催化氧化体系对挥发性有机污染物的降解效率、矿化程度和长期运行稳定性,同时实现了废弃生物质资源的高值化利用;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1777275996234-000001
    Figure REF-OBJ-1777275996234-000001
  • Figure REF-OBJ-1777275996234-000002
    Figure REF-OBJ-1777275996234-000002
  • Figure REF-OBJ-1777275996234-000003
    Figure REF-OBJ-1777275996234-000003
Patent Text Reader

Abstract

The present application relates to a kind of composite metal catalyst and its preparation method and application in ozone catalytic oxidation, and the preparation method is specifically, cocoa pod shell and amaranth are cleaned, dried and crushed to obtain mixed plant powder, then treated by soaking with acid solution, and then washed to neutral and dried to obtain pretreated mixed plant powder;Tetrabutyl titanate, anhydrous ethanol, deionized water and concentrated nitric acid are mixed in proportion, ceramic sol is obtained by hydrolysis at room temperature;The pretreated plant powder is treated by negative pressure impregnation with ceramic sol, and then aged by standing, dried, calcined and cooled to obtain a composite biomass charcoal carrier with hierarchical porous structure;It is immersed in manganese salt solution and chromium salt solution, and a composite metal catalyst is obtained after calcination treatment.The composite metal catalyst of the present application has hierarchical porous structure, high mechanical stability and double-metal synergistic catalytic effect, which significantly improves the degradation efficiency of volatile organic pollutants and the long-term operation stability of ozone catalytic oxidation system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, specifically relating to a composite metal catalyst, its preparation method, and its application in ozone catalytic oxidation. Background Technology

[0002] Volatile organic compounds (VOCs), as important precursors to ozone and PM2.5, have become one of the core challenges in global air pollution control. Toluene, a typical aromatic VOC, is widely derived from industries such as petrochemicals, paint printing, and furniture manufacturing. It is characterized by high toxicity and difficulty in degradation, posing a serious threat to human health and the ecological environment. Currently, VOCs treatment technologies mainly include adsorption, incineration, photocatalytic oxidation, and ozone catalytic oxidation. Among these, adsorption methods suffer from problems such as the need for frequent replacement of adsorbents after adsorption saturation and the potential for secondary pollution; incineration methods have high energy consumption and operating costs, and may produce secondary pollutants such as nitrogen oxides; photocatalytic oxidation methods are limited by bottlenecks such as narrow light response range and low quantum efficiency.

[0003] Ozone catalytic oxidation technology has become a research hotspot for the in-depth treatment of VOCs in recent years due to its advantages such as mild reaction conditions, strong oxidizing power, and non-selectivity. This technology promotes the decomposition of ozone through a catalyst to generate hydroxyl radicals (·OH) and singlet oxygen (·OH). 1 Strong oxidizing active species such as O2 can completely mineralize VOCs into harmless substances such as CO2 and H2O. In the ozone catalytic oxidation system, the performance of the catalyst is the key factor that determines the degradation efficiency.

[0004] Manganese oxides exhibit excellent catalytic activity in ozone decomposition due to their rich valence state variations, superior redox properties, and high oxygen vacancy concentration, effectively degrading various organic pollutants. However, single manganese-based catalysts suffer from problems such as easy aggregation of active sites, limited specific surface area, and insufficient stability. Studies have shown that introducing a second metal (such as Cr, Ce, or Fe) to form a bimetallic composite catalyst can enhance electron transfer capabilities and improve catalytic activity and stability through the synergistic effect between metals. Furthermore, the catalyst support structure has a significant impact on catalytic performance. Biochar, as a widely available, low-cost, and environmentally friendly porous carbon material, possesses abundant pore structures and surface functional groups, making it an ideal choice for catalyst support preparation. However, the specific surface area and pore structure of traditional biochar are poorly controllable, resulting in uneven dispersion of active components and limited catalytic efficiency when used directly as a support. Therefore, how to control the pore structure of biochar through reasonable preparation processes and synergistically optimize the loading mode of bimetallic active components to construct an efficient and stable ozone catalytic oxidation system remains a pressing technical problem to be solved. Summary of the Invention

[0005] The purpose of this invention is to provide a composite metal catalyst, its preparation method, and its application in ozone catalytic oxidation in order to solve the above-mentioned problems, thereby addressing the shortcomings of the prior art.

[0006] The present invention achieves the above objectives through the following technical solutions: This invention provides a method for preparing a composite metal catalyst, comprising the following steps: Step 1: Wash, dry, and crush the cocoa pod shells and amaranth separately, and then mix them to obtain mixed plant powder. Soak the mixed plant powder in an acid solution, wash it until it is neutral, and then dry it to obtain pretreated mixed plant powder. Step 2: Mix tetrabutyl titanate, anhydrous ethanol, deionized water and concentrated nitric acid in a certain proportion, and stir at room temperature to hydrolyze and obtain ceramic sol. Step 3: The pretreated plant powder is impregnated under negative pressure using the ceramic sol, and then subjected to static aging, drying, calcination and cooling to obtain a composite biochar support with a hierarchical porous structure. Step 4: The composite biochar support is impregnated in manganese salt solution and chromium salt solution, and after stirring and calcination, a composite metal catalyst is obtained.

[0007] As a further optimization of the present invention, in step one, the mass ratio of cocoa pod shell powder to amaranth plant powder in the mixed plant powder is 1-3:1; the particle size of the mixed plant powder is 0.5-2mm.

[0008] As a further optimization of the present invention, in step one, the acid solution soaking treatment is to soak in at least one of hydrochloric acid or sulfuric acid with a mass concentration of 5-15% for 2-6 hours.

[0009] As a further optimization of the present invention, in step two, the molar ratio of tetrabutyl titanate, anhydrous ethanol, deionized water and concentrated nitric acid is 1:(10-20):(2-5):(0.01-0.05).

[0010] As a further optimization of the present invention, in step three, the negative pressure impregnation treatment is impregnation for 30-60 minutes under conditions of -0.08 to -0.1 MPa; The solid-liquid ratio of the ceramic sol to the pretreated plant powder is 1:8-12; The static aging process is performed under normal pressure for 12-24 hours; the drying process is performed at 60-80℃ for 12-24 hours. The calcination process involves heating the temperature to 500-700℃ at a rate of 2-5℃ / min and calcining in an inert atmosphere for 3-5 hours.

[0011] As a further optimization of the present invention, in step four, a stepwise impregnation method is adopted, in which the composite biochar support carrier is impregnated in a manganese salt solution with a concentration of 0.1-0.5 mol / L, stirred at room temperature for 2-4 h, dried at 80-120℃ for 8-15 h, and calcined at 400-500℃ for 2-3 h to obtain an intermediate loaded with manganese oxide. The intermediate was impregnated in a chromium salt solution with a concentration of 0.05-0.2 mol / L, stirred at room temperature for 2-4 h, dried at 80-120 °C for 8-15 h, and calcined at 450-550 °C for 2-3 h to obtain a manganese-chromium bimetallic ozone oxidation catalyst. The solid-liquid ratio of the composite biochar support carrier to the manganese salt solution with a concentration of 0.1-0.5 mol / L and the chromium salt solution with a concentration of 0.05-0.2 mol / L is 1:(8-12):(8-12).

[0012] The present invention also provides a composite metal catalyst, which is prepared by the above-described preparation method.

[0013] This invention also provides an application of a composite metal catalyst in ozone catalytic oxidation.

[0014] As a further optimization of the present invention, the composite metal catalyst is subjected to a catalytic reaction for 1-24 hours under the catalytic conditions of a mixture of toluene and nitrogen, a mixture of ozone and oxygen, a temperature of 20-35°C, a relative humidity of 45%-65%, and a gas reaction flow rate of 450-650 mL / min, with a toluene removal rate ≥86% and an ozone decomposition rate ≥92%.

[0015] The beneficial effects of this invention are as follows: 1) This invention uses cocoa pod shells and amaranth as composite biomass. Through multi-level process control, such as acid pretreatment to synergistically create pores, ceramic sol negative pressure impregnation to modify the pore structure, and manganese-chromium bimetallic stepwise loading activation, a composite metal catalyst with hierarchical porous structure, high mechanical stability and bimetallic synergistic catalytic effect is constructed. This significantly improves the degradation efficiency, mineralization degree and long-term operational stability of ozone catalytic oxidation system for volatile organic pollutants, while realizing the high-value utilization of waste biomass resources. 2) This invention utilizes the synergistic pore-forming effect of cocoa pod shells and amaranth, combined with the pore structure modification of ceramic sol, to successfully construct a hierarchical porous composite biochar support with high specific surface area, large pore volume, and suitable pore size distribution. This effectively solves the technical problems of single biomass materials having a single pore structure and limited specific surface area, and also provides an ideal structural basis for the efficient dispersion and catalytic reaction of subsequent manganese-chromium bimetallic active components. 3) The composite metal catalyst provided by this invention maintains high catalytic activity and excellent stability under 24-hour continuous operation conditions through the robust porous support structure constructed by cocoa pod shells and amaranth, the framework stability enhanced by ceramic sol, and the synergistic stabilizing effect of manganese and chromium bimetals. This fully demonstrates its good potential for practical engineering applications. 4) This invention uses agricultural waste as the main raw material, realizing the high-value utilization of waste biomass resources. It is easy to operate, has mild conditions, is easy to scale up, and has good economic and environmental benefits. Detailed Implementation

[0016] The present application will now be described in further detail. It should be noted that the following specific embodiments are only used to further illustrate the present application and should not be construed as limiting the scope of protection of the present application. Those skilled in the art can make some non-essential improvements and adjustments to the present application based on the above application content.

[0017] I. Materials 1. Acid solution: at least one of hydrochloric acid or sulfuric acid with a mass concentration of 5-15%; 2. Mixed plant powder: The mass ratio of cocoa (Theobroma cacao L.) pod shell powder to amaranth (Amaranthus spinosus L.) powder (specifically, the above-ground parts of the amaranth plant; the content of heavy metal elements such as Cd, Cr, Cu, Pb, As, and Ni in the amaranth plant was determined using inductively coupled plasma atomic emission spectrometry, and the results showed that the total heavy metal content was ≤5mg / Kkg) was 1-3:1, and the particle size of the mixed plant powder was 0.5-2mm; 3. Preparation of ceramic sol: raw materials: tetrabutyl titanate, anhydrous ethanol, deionized water and concentrated nitric acid are prepared in a molar ratio of 1:(10-20):(2-5):(0.01-0.05); Unless otherwise specified, all methods used in this application are conventional methods known to those skilled in the art, and all reagents and materials used are commercially available products unless otherwise specified.

[0018] III. Methods Example 1

[0019] In this embodiment, a method for preparing a composite metal catalyst is provided, comprising the following steps: Step 1: Wash, dry, crush, and mix cocoa pod shells and amaranth plants separately to obtain mixed plant powder (the mass ratio of cocoa pod shell powder to amaranth plant powder is 1:1). Soak the mixed plant powder in a 10% acid solution for 5 hours, wash until neutral, and dry at 80°C to obtain pretreated mixed plant powder. Step 2: Mix 50 mL of tetrabutyl titanate, 170 mL of anhydrous ethanol, 12 mL of deionized water and 0.35 mL of concentrated nitric acid, and stir at room temperature for 3.5 h to hydrolyze and obtain ceramic sol. Step 3: Immerse 50g of pretreated plant powder obtained in Step 1 into 500mL of ceramic sol obtained in Step 2, and impregnate for 45min under vacuum of -0.1MPa. Then, age the mixture under normal pressure for 18h. Dry the aged mixture at 75℃ for 20h, then heat it to 620℃ at a heating rate of 5℃ / min, and calcine it in an inert atmosphere (N2) for 3.5h. After cooling, obtain a composite biochar support with a hierarchical porous structure. Step 4: Impregnate 20g of the composite biochar support obtained in Step 3 in 200mL of a 0.3mol / L manganese salt solution (Mn(NO3)2), stir at room temperature for 3.5h, dry at 90℃ for 10h, and then calcine at 450℃ for 2.5h to obtain an intermediate supported on manganese oxide. Impregnate the intermediate in 200mL of a 0.15mol / L chromium salt solution (Cr(NO3)3), stir at room temperature for 3h, dry at 110℃ for 12h, and then calcine at 480℃ for 2.5h to obtain a composite metal catalyst (a manganese-chromium bimetallic catalyst supported on a composite biochar support). Example 2

[0020] In this embodiment, a method for preparing a composite metal catalyst is provided, comprising the following steps: Step 1: Wash, dry, crush, and mix cocoa pod shells and amaranth plants separately to obtain mixed plant powder (the mass ratio of cocoa pod shell powder to amaranth plant powder is 2:1). Soak the mixed plant powder in a 10% acid solution for 5 hours, wash until neutral, and dry at 80°C to obtain pretreated mixed plant powder. Step 2: Mix 50 mL of tetrabutyl titanate, 130 mL of anhydrous ethanol, 9 mL of deionized water and 0.25 mL of concentrated nitric acid, and stir at room temperature for 3.5 h to hydrolyze and obtain ceramic sol. Step 3: Immerse 50g of pretreated plant powder obtained in Step 1 into 500mL of ceramic sol obtained in Step 2, and impregnate for 45min under vacuum of -0.1MPa. Then, age the mixture under normal pressure for 18h. Dry the aged mixture at 75℃ for 20h, then heat it to 620℃ at a heating rate of 5℃ / min, and calcine it in an inert atmosphere (N2) for 3.5h. After cooling, obtain a composite biochar support with a hierarchical porous structure. Step 4: Impregnate 20g of the composite biochar support obtained in Step 3 in 200mL of a 0.3mol / L manganese salt solution (Mn(NO3)2), stir at room temperature for 3.5h, dry at 90℃ for 10h, and then calcine at 450℃ for 2.5h to obtain an intermediate supported on manganese oxide. Impregnate the intermediate in 200mL of a 0.15mol / L chromium salt solution (Cr(NO3)3), stir at room temperature for 3h, dry at 110℃ for 12h, and then calcine at 480℃ for 2.5h to obtain a composite metal catalyst (a manganese-chromium bimetallic catalyst supported on a composite biochar support). Example 3

[0021] In this embodiment, a method for preparing a composite metal catalyst is provided, comprising the following steps: Step 1: Wash, dry, crush, and mix cocoa pod shells and amaranth plants separately to obtain mixed plant powder (the mass ratio of cocoa pod shell powder to amaranth plant powder is 3:1). Soak the mixed plant powder in a 10% acid solution for 5 hours, wash until neutral, and dry at 80°C to obtain pretreated mixed plant powder. Step 2: Mix 50 mL of tetrabutyl titanate, 100 mL of anhydrous ethanol, 6 mL of deionized water and 0.15 mL of concentrated nitric acid, and stir at room temperature for 3.5 h to hydrolyze and obtain ceramic sol. Step 3: Immerse 50g of pretreated plant powder obtained in Step 1 into 500mL of ceramic sol obtained in Step 2, and impregnate for 45min under vacuum of -0.1MPa. Then, age the mixture under normal pressure for 18h. Dry the aged mixture at 75℃ for 20h, then heat it to 620℃ at a heating rate of 5℃ / min, and calcine it in an inert atmosphere (N2) for 3.5h. After cooling, obtain a composite biochar support with a hierarchical porous structure. Step 4: Impregnate 20g of the composite biochar support obtained in Step 3 in 200mL of a 0.3mol / L manganese salt solution (Mn(NO3)2), stir at room temperature for 3.5h, dry at 90℃ for 10h, and then calcine at 450℃ for 2.5h to obtain an intermediate supported on manganese oxide. Impregnate the intermediate in 200mL of a 0.15mol / L chromium salt solution (Cr(NO3)3), stir at room temperature for 3h, dry at 110℃ for 12h, and then calcine at 480℃ for 2.5h to obtain a composite metal catalyst (a manganese-chromium bimetallic catalyst supported on a composite biochar support).

[0022] Comparative Example 1 In this comparative example, the preparation method is the same as in Example 2. The difference from Example 2 is that only one biomass material is used, namely cocoa pod shells, that is, cocoa pod shell powder is used instead of amaranth plant powder in equal parts by mass. Everything else is consistent with Example 2.

[0023] Comparative Example 2 In this comparative example, the preparation method is the same as in Example 2. The difference from Example 2 is that only one biomass material is used, namely amaranth. That is, the cocoa pod shell powder is replaced with an equal mass of amaranth plant powder. Everything else is consistent with Example 2.

[0024] Comparative Example 3 In this comparative example, the preparation method is the same as in Example 2. The difference from Example 2 is that two biomass materials are used, namely, cocoa pod shells and quinoa, that is, quinoa plant powder is replaced with amaranth plant powder in equal parts by mass. Everything else is consistent with Example 2.

[0025] Comparative Example 4 In this comparative example, the preparation method is the same as in Example 2. The difference from Example 2 is that two biomass materials are used, namely coconut shell and amaranth. That is, coconut shell powder is used instead of cocoa pod shell powder in equal parts by mass. Everything else is consistent with Example 2.

[0026] Comparative Example 5 In this comparative example, a method for preparing a composite metal catalyst is provided, comprising the following steps: Step 1: Wash, dry, crush, and mix cocoa pod shells and amaranth plants separately to obtain mixed plant powder (the mass ratio of cocoa pod shell powder to amaranth plant powder is 2:1). Soak the mixed plant powder in a 10% acid solution for 5 hours, wash until neutral, and dry at 80°C to obtain pretreated mixed plant powder. Step 2: The pretreated mixed plant powder is heated to 620°C at a heating rate of 5°C / min and calcined in an inert atmosphere (N2) for 3.5 h. After cooling, a composite biochar support with a hierarchical porous structure is obtained. Step 3: Impregnate 20g of the composite biochar support obtained in Step 2 in 200mL of a 0.3mol / L manganese salt solution (Mn(NO3)2), stir at room temperature for 3.5h, dry at 90℃ for 10h, and then calcine at 450℃ for 2.5h to obtain an intermediate supported on manganese oxide. Impregnate the intermediate in 200mL of a 0.15mol / L chromium salt solution (Cr(NO3)3), stir at room temperature for 3h, dry at 110℃ for 12h, and then calcine at 480℃ for 2.5h to obtain a composite metal catalyst (a manganese-chromium bimetallic catalyst supported on a composite biochar support).

[0027] Comparative Example 6 In this comparative example, the preparation method is the same as in Example 2. The difference from Example 2 is that an equal volume and concentration of nickel salt (Ni(NO3)2) solution is used instead of chromium salt (Cr(NO3)3) solution; all other aspects are the same as in Example 2.

[0028] Comparative Example 7 In this comparative example, the preparation method is the same as in Example 2. The difference from Example 2 is that an equal volume and concentration of molybdenum salt (Mo(NO3)3) solution is used instead of chromium salt (Cr(NO3)3) solution; all other aspects are the same as in Example 2.

[0029] Experimental Test (1) Test of pore structure performance of each catalyst group The pore structure parameters of each catalyst group were determined using a fully automated specific surface area and porosity analyzer (Micromeritics ASAP 2460). The experimental data are shown in Table 1. Table 1. Test data on the pore structure properties of each catalyst group Experimental conclusions: As shown in Table 1, the composite metal catalysts prepared in Examples 1-3 of this invention all exhibit excellent porous structure characteristics, with Example 2 being the best. Verification shows that single biomass materials are difficult to form an ideal hierarchical porous structure, while the combination of cocoa pod shells and amaranth has specific advantages. The two can produce a synergistic pore-forming effect during acid treatment and calcination, forming a more developed porous network structure. In addition, the ceramic sol formed by the hydrolysis of tetrabutyl titanate can effectively fill and modify the pore structure of biochar during negative pressure impregnation. After high-temperature calcination, a TiO2 ceramic skeleton is formed, which significantly improves the specific surface area and pore volume of the support and constructs a hierarchical porous structure. The use of manganese salts or chromium salts also has a certain influence on the fine control of the pore structure of the support.

[0030] (2) Catalytic performance test of each group of catalysts Experimental equipment and conditions: A fixed-bed continuous flow reactor was used to evaluate the catalytic performance. The reactor body was a quartz tube with an inner diameter of 10 mm. The catalyst bed was located in the middle of the reactor, with quartz wool underneath to support the catalyst. The catalyst loading was 1.0 g. The reaction temperature could be precisely controlled within the range of room temperature to 150 °C using a temperature controller in conjunction with a heating furnace. The flow rates of each gas were controlled by mass flow meters, including the carrier gas (high-purity nitrogen), the pollutant gas (a mixture of toluene and nitrogen), and the ozone and oxygen mixture (ozone was generated on-site using pure oxygen from an ozone generator). N2 was used as the balance gas. The toluene concentration at the reactor inlet was 100 ppm, the ozone concentration at the reactor inlet was 200 ppm, the total reaction flow rate was 500 mL / min, and the corresponding space velocity was 30,000 h⁻¹. -1 The relative humidity of the reaction system was controlled at 50%, and the reaction temperature was set to room temperature (25℃) to simulate actual environmental conditions.

[0031] Detection methods: The concentration of toluene in the reactor outlet gas was quantitatively analyzed using gas chromatography-FID (GC-FID); the concentrations of carbon dioxide and carbon monoxide were detected using gas chromatography-TCD (GC-TCD) to calculate CO2 selectivity; the ozone concentration at the reactor outlet was monitored online using an ultraviolet ozone analyzer; to detect hydroxyl radicals (·OH) generated in the catalytic system, electron spin resonance (ESR) spectroscopy combined with spin trapping was used, with DMPO (5,5-dimethyl-1-pyrrolline-N-oxide) as the trapping agent, to analyze the types and relative intensities of free radicals in the reaction system.

[0032] Experimental Procedure: 1.0g of catalyst was loaded into the reactor, and high-purity nitrogen gas was introduced. The reactor was pretreated at 150℃ for 1 hour to remove adsorbed moisture and impurities from the catalyst surface. After pretreatment, the reactor was cooled to the set reaction temperature (25℃). Subsequently, a mixture of toluene and ozone was introduced, and the flow rates of each gas were adjusted to preset values. The reactor was run stably for 30 minutes to allow the reaction system to reach a steady state. After reaching steady state, the concentrations of toluene, CO, CO2, and ozone in the outlet gas were continuously monitored, with data recorded every 10 minutes for 60 minutes. Under the same experimental conditions, experiments were conducted on each example group, comparative group, and blank group (without catalyst). The calculation formulas are as follows: Toluene removal rate = [(toluene concentration at reactor inlet - toluene concentration at reactor outlet) / toluene concentration at reactor inlet] × 100%; CO2 selectivity = [reactor outlet CO2 concentration / 7 × (toluene consumption)] × 100%; Ozone decomposition rate = [(reactor inlet ozone concentration - reactor outlet ozone concentration) / reactor inlet ozone concentration] × 100%; The relative intensity of hydroxyl radicals = the peak area of ​​the characteristic peak of the DMPO-OH adduct in the ESR spectrum of the sample loaded with the catalyst to be tested / the peak area of ​​the characteristic peak of the DMPO-OH adduct in the ESR spectrum of the blank group without catalyst measured under the same conditions; The experimental data for toluene removal rate (%), ozone decomposition rate (%), CO2 selectivity (%), and relative strength of hydroxyl radicals (·OH) are shown in Table 2: Table 2. Catalyst Experimental Data Recording Table for Each Group Experimental Conclusions: As shown in Table 1, the composite metal catalysts prepared in Examples 1-3 of this invention all exhibited excellent catalytic performance in the ozone oxidation system. Among them, Example 2 showed the best effect, with a toluene removal rate of 95.1%, a CO2 selectivity of 91.2%, and an ozone decomposition rate as high as 98.5%. In contrast, the toluene removal rate, ozone decomposition rate, CO2 selectivity, and relative strength of hydroxyl radicals were significantly reduced when using only cocoa pod shells, amaranth, or other biomass materials as biochar support carriers. This indicates that the combination of cocoa pod shells and amaranth selected in this invention has specific advantages, and can efficiently catalyze the decomposition of ozone to generate a large number of hydroxyl radicals and elemental oxygen and other highly oxidizing active species. The gaseous pollutant toluene is completely oxidized into CO2, H2O, and other non-toxic, harmless, and odorless substances, achieving a highly efficient and thorough catalytic oxidation process. In addition, the lack of ceramic sol treatment significantly reduced the toluene removal rate, ozone decomposition rate, CO2 selectivity, and relative strength of hydroxyl radicals, confirming that ceramic sol treatment is crucial. Furthermore, experiments showed that the manganese-chromium bimetallic combination has the best synergistic catalytic effect. In summary, the composite metal catalyst provided by this invention significantly improves the degradation efficiency of gaseous pollutants in the ozone oxidation system through the synergistic catalytic effect of manganese-chromium bimetals and the structural advantages of the hierarchical porous ceramic support, and has good prospects for environmental application.

[0033] (3) Stability test of each group of catalysts After the system ran continuously for 24 hours, it was tested again. The experimental data for 24-hour toluene removal rate (%), 24-hour ozone decomposition rate (%), 24-hour CO2 selectivity (%), and 24-hour relative strength of hydroxyl radicals are shown in Table 3. Table 3. Catalyst stability test data (after 24 hours of operation) for each group. Experimental conclusion: After 24 hours of continuous operation, the composite metal catalysts prepared in Examples 1-3 of this invention still maintain excellent catalytic activity. Compared with the initial performance, the decline of various indicators is small, showing excellent long-term operational stability.

[0034] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a composite metal catalyst, characterized in that: Includes the following steps: Step 1: Wash, dry, and crush the cocoa pod shells and amaranth separately, and then mix them to obtain mixed plant powder. Soak the mixed plant powder in an acid solution, wash it until it is neutral, and then dry it to obtain pretreated mixed plant powder. Step 2: Mix tetrabutyl titanate, anhydrous ethanol, deionized water and concentrated nitric acid in a certain proportion, and stir at room temperature to hydrolyze and obtain ceramic sol. Step 3: The pretreated plant powder is impregnated under negative pressure using the ceramic sol, and then subjected to static aging, drying, calcination, and cooling to obtain a composite biochar support carrier with a hierarchical porous structure. Step 4: The composite biochar support is impregnated in manganese salt solution and chromium salt solution, and after stirring and calcination, a composite metal catalyst is obtained.

2. The method for preparing a composite metal catalyst according to claim 1, characterized in that: In step one, the mass ratio of cocoa pod shell powder to amaranth plant powder in the mixed plant powder is 1-3:1; the particle size of the mixed plant powder is 0.5-2 mm.

3. The method for preparing a composite metal catalyst according to claim 1, characterized in that: In step one, the acid solution soaking treatment is to soak in at least one of hydrochloric acid or sulfuric acid with a mass concentration of 5-15% for 2-6 hours.

4. The method for preparing a composite metal catalyst according to claim 1, characterized in that: In step two, the molar ratio of tetrabutyl titanate, anhydrous ethanol, deionized water and concentrated nitric acid is 1:(10-20):(2-5):(0.01-0.05).

5. The method for preparing a composite metal catalyst according to claim 4, characterized in that: In step three, the negative pressure impregnation treatment is to impregnate for 30-60 minutes under conditions of -0.08 to -0.1 MPa. The solid-liquid ratio of the ceramic sol to the pretreated plant powder is 1:8-12; The static aging process is performed under normal pressure for 12-24 hours; the drying process is performed at 60-80℃ for 12-24 hours. The calcination process involves heating the temperature to 500-700℃ at a rate of 2-5℃ / min and calcining in an inert atmosphere for 3-5 hours.

6. The method for preparing a composite metal catalyst according to claim 1, characterized in that: In step four, a stepwise impregnation method is adopted, in which the composite biochar support carrier is impregnated in a manganese salt solution with a concentration of 0.1-0.5 mol / L, stirred at room temperature for 2-4 h, dried at 80-120℃ for 8-15 h, and calcined at 400-500℃ for 2-3 h to obtain an intermediate loaded with manganese oxides. The intermediate was impregnated in a chromium salt solution with a concentration of 0.05-0.3 mol / L, stirred at room temperature for 2-4 h, dried at 80-120 °C for 8-15 h, and calcined at 450-550 °C for 2-3 h to obtain a manganese-chromium bimetallic ozone oxidation catalyst. The solid-liquid ratio of the composite biochar support carrier to the manganese salt solution with a concentration of 0.1-0.5 mol / L and the chromium salt solution with a concentration of 0.05-0.3 mol / L is 1:(8-12):(8-12).

7. A composite metal catalyst, characterized in that: It is prepared by any one of the preparation methods described in claims 1-6.

8. The application of the composite metal catalyst as described in claim 7 in ozone catalytic oxidation.

9. The application according to claim 8, characterized in that: The composite metal catalyst, under the catalytic conditions of a mixture of toluene and nitrogen, and a mixture of ozone and oxygen, at a temperature of 20-35℃, a relative humidity of 45%-65%, and a gas reaction flow rate of 450-650 mL / min, undergoes a catalytic reaction for 1-24 hours, achieving a toluene removal rate ≥86% and an ozone decomposition rate ≥92%.